Biegły psycholog a odebranie i ocena zeznań małoletniego świadka w procesie karnym - Żylińska, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Evidence of an underage witness may play a vital role in criminal proceedings in ascertaining the circumstances of an incident. The achievement of this goal is undoubtedly determined by the way a child is questioned — a way that takes into account the procedural and tactical rules of questioning juveniles, bearing in mind the psychological aspects of the formation of underage witness’ testimony. What is also important is a critical approach to its credibility.All this requires active participation of an expert psychologist who can assess the witness’ personality, observation and reconstruction skills, and thus can provide the relevant institution with additional material which can be used to evaluate the credibility of the evidence of an underage witness.
Keywords: dowód (prawo karne); świadek małoletni; biegły psycholog; postępowanie karne